Growth and characterisation of platinum and palladium catalysed silicon based nanostructures for nano-device fabrication - Khumalo, Zakhelumuzi Mesuli (Department of Physics, 2019)
This thesis first describes the application of ion beam techniques for the analysis of synthesised metal silicide nano-droplets which are used to synthesis silicon nanowires. This analysis was performed for both Molecular Beam Epitaxy (MBE) and Electron Beam Evaporator (EBE) deposited metal coated silicon substrates. The formation of platinum silicide phases as a function of annealing temperature and time was investigated using in situ real-time Rutherford Backscattering Spectrometry (RBS). In situ real-time RBS revealed the reaction of platinum and silicon to start at about 200 °C and 230 °C, for MBE and EBE coatings respectively, forming platinum silicide phases (Pt2Si and PtSi) in sequence. Further analysis on the EBE deposited coatings using a scanning electron microscope confirmed the formation of droplets at 800 °C. Particle induced X-ray emission analysis showed the variation of platinum concentration, in droplets regions, between 1600 and 2000 counts. The surrounding regions were left almost uncovered due to platinum coating dewetting. Work was then carried out to investigate the growth of silicon nanowires from the produced droplets. Silicon nanowires were observed to form at 800 °C and 1000 °C using pulsed laser ablation and thermal annealing techniques, respectively, for the EBE deposited coatings. Furthermore, MBE was shown to produce self-aligned platinum silicide (PtSi) nanoclusters and nanowires on Si (111) substrates near the eutectic point (T = 978 °C and 67 at% Si) of the platinum silicon system. With an added silicon source in the MBE annealing chamber, the formation of two different silicon steps (straight and wave-like) is reported. The steps determine the position and the shape of the thermomigrating PtSi droplets. Nanoclusters preferentially form in the triple point of the wave-like steps while nanoclusters that form on the straight steps combine and grow into silicide nanowires. We report, for the platinum (MBE deposited) catalysed core-shell silicon nanowires, a reproducible method for eliminating hazardous acids during lithography device preparation with the use of silicide forming metal. With regard to palladium coatings, self-aligned polycrystalline palladium-silicide nanowires and palladium catalysed crystalline core-amorphous shell silicon nanowires were synthesised. The catalyst (palladium) was deposited on a silicon substrate using MBE. As a result of thermal annealing in the silicon flux, self-aligned and fully crystalline palladium-silicide nanowires were synthesised while crystalline core-amorphous shell silicon nanowires were grown when an argon gas was introduced. These results highlight the mechanisms to synthesise specific types of nanowires to be used in a variety of electronic devices depending on their applications. Furthermore, for the application of the produced core-shell nanowires in nanodevice fabrication, we present two approaches to reduce the oxidation of the nanowires during the thermal annealing growth method. The ratios of the amorphous shell to crystalline core on the nanowires produced, from the two methods, are compared and show a remarkable drop in oxide thickness when compared to nanowires fabricated using the current techniques available. In addition, focused ion beam was utilised to contact the oxide reduced nanowires, without first removing the thin oxide shell, for transport measurements. The oxygen reduced core-shell silicon nanowires showed very low electrical resistivity (4×10-1 Ω.cm). The techniques employed presents a new alternative to the production of low cost, high yield, high conducting silicon nanowires that will find use in a range of semiconductor based technology.